2014
DOI: 10.2320/matertrans.mg201415
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effects of TiCl<sub>3</sub> on Dehydrogenation Reaction of LiAlH<sub>4</sub>

Abstract: Recently, LiAlH 4 has attracted attention as one of the most promising hydrogen storage materials, because LiAlH 4 is able to release large amount of hydrogen (7.9 mass%H 2 ) below 250°C. However, the kinetics of the dehydrogenation reaction of LiAlH 4 is too slow for applications to fuel cell vehicles. To improve the dehydrogenation kinetics, the dopant effect of TiCl 3 has been investigated in this research. Here, LiAlH 4 doped with various ratios (0, 0.1, 0.2, 0.5, 1.0, and 2.0 mol%) of TiCl 3 were prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Since Bogdanović et al reported an absence of hysteresis and nearly horizontal pressure plateaus in the TiCl 3 -doped NaAlH 4 [7], many researchers have studied complex hydrides including alanate as potential reversible hydrogen storage materials. In the case of LiAlH 4 , the improved desorption kinetics was reported by the doping of Ti catalyst using mechanically milling [10][11][12]. Recent study also reported a single step hydrogen release of LiAlH 4 , which was induced by the synergetic effects of Ti catalytic coating and nanosizing effects [13].…”
Section: Introductionmentioning
confidence: 95%
“…Since Bogdanović et al reported an absence of hysteresis and nearly horizontal pressure plateaus in the TiCl 3 -doped NaAlH 4 [7], many researchers have studied complex hydrides including alanate as potential reversible hydrogen storage materials. In the case of LiAlH 4 , the improved desorption kinetics was reported by the doping of Ti catalyst using mechanically milling [10][11][12]. Recent study also reported a single step hydrogen release of LiAlH 4 , which was induced by the synergetic effects of Ti catalytic coating and nanosizing effects [13].…”
Section: Introductionmentioning
confidence: 95%
“…Among alanates, LiAlH 4 has a relatively high theoretical hydrogen density (10.5 wt.%) [18] in comparison with NaAlH 4 (7.4 wt.%) and KAlH 4 (5.7 wt.%) [19]. By the two-step decomposition reaction, 7.97 wt.% hydrogen could be released from LiAlH 4 at moderate temperature (160e220 C) [20,21].…”
Section: Introductionmentioning
confidence: 96%
“…Based on the dehydrogenation study, LiAlH 4 doped with 0.5 mol% TiCl 3 displays the largest decrement in the onset decomposition temperature and starts to desorb hydrogen at 91 C, which is 88 C lower than the as-received LiAlH 4 . Meanwhile, LiAlH 4 + 0.5 mol% Ti shows the least reduction with an initial dehydrogenation temperature of 119 C. Furthermore, Isobe et al 41 studied the dehydrogenation of LiAlH 4 doped with various ratios of TiCl 3 (0, 0.1, 0.2, 0.5, 1.0, and 2.0 mol%). They report that the most effective amount of TiCl 3 in enhancing the desorption properties of LiAlH 4 is 0.2 mol%.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, LiAlH 4 + 0.5 mol% Ti shows the least reduction with an initial dehydrogenation temperature of 119°C. Furthermore, Isobe et al 41 studied the dehydrogenation of LiAlH 4 doped with various ratios of TiCl 3 (0, 0.1, 0.2, 0.5, 1.0, and 2.0 mol%). They report that the most effective amount of TiCl 3 in enhancing the desorption properties of LiAlH 4 is 0.2 mol%.…”
Section: Introductionmentioning
confidence: 99%